Quercetin Exhibits Broad-Spectrum Antibiofilm and Antiquorum Sensing Activities Against Gram-Negative Bacteria: In Vitro and In Silico Investigation Targeting Antimicrobial Therapy - Tanvi Shastri; Reem Binsuwaidan; Arif Jamal Siddiqui; Riadh Badraoui; Sadaf Jahan; Nawaf Alshammari; Mohd Adnan; Mitesh Patel (Canadian Journal of Infectious Diseases and Medical Microbiology)
Quercetin (QC), a flavonoid abundant in fruits and vegetables, has garnered attention for its potential therapeutic properties. In this study, we investigated the antibiofilm and antiquorum sensing (QS) activities of QC against Gram-negative bacteria both in vitro and in silico. The findings of this study demonstrate MIC values of 125 μg/mL for Chromobacterium violaceum, 250 μg/mL for Pseudomonas aeruginosa, and 500 μg/mL for Serratia marcescens, indicating its antibacterial potential abilities. QS-mediated production of violacein and prodigiosin was significantly inhibited in a dose-dependent manner at sub-MIC concentrations. Additionally, a dose-dependent reduction in the virulence factors of P. aeruginosa, including production of pyocyanin, pyoverdine, and rhamnolipid, was noted with QC. Biofilm formation decreased by 66.40%, 59.28%, and 63.70% at the highest sub-MIC for C. violaceum, P. aeruginosa, and S. marcescens, respectively. Furthermore, swimming motility and exopolysaccharide (EPS) production were also reduced in the presence of QC. Additionally, molecular docking and molecular dynamics simulations elucidate the binding interactions between QC and key molecular targets (LasI, LasR, PilY1, LasA, PilT, CviR, CviR′, PqsR, RhlR, and PigG) involved in biofilm formation and QS pathways. Our results indicated that the antibiofilm and anti-QS sensing activities of QC may be attributed to its ability to interfere with critical signaling molecules and regulatory proteins. Overall, this study highlights QC as a promising natural compound for combating biofilm-associated infections caused by Gram-negative bacteria. The multifaceted antimicrobial mechanisms of QC underscore its potential as a therapeutic agent for the treatment of biofilm-related infections, providing the way for further exploration, and development of QC-based strategies in antimicrobial therapy.